Investigatins the impact of using PMIS in resource management on cost of projects as a conceptual model in construction projects - Mosavi, Seyed Karim; Hosseini, Azim; Vosoughifar, Hamid Reza; Barandoust, Rambood; Mohammadi, Ghodratollah (Nexo Revista Científica, 2022)
The Project Management Information System (PMIS) is a powerful tool in project management discussions due to its many benefits. Improper deployment of a PMIS and disregard for its qualitative factors influencing project success will never lead to the achievement of project goals. The purpose of this study was to investigate the impact of using PMIS on the cost management of construction projects that have used this information system. In this study, the impact of PMIS quality factors such as project quality, level of implementation technology, level of design skills, teamwork coefficient and execution time on project cost management was evaluated. The statistical population is the questionnaire of projects implemented through PMIS in construction projects, based on which 100 questionnaires were distributed among the projects and then collected. In this study, structural equation modeling has been used to investigate the research hypotheses. In this regard, "SPSS" software was used. The results of this study indicate that system quality, information quality and service quality have a positive effect on project success in terms of cost management.